2016
DOI: 10.1007/s13365-015-0413-4
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and in vitro activity of HIV-1 latency-reversing agents in primary CNS cells

Abstract: Despite the success of combination antiretroviral therapy (cART), HIV persists in long lived latently infected cells in the blood and tissue, and treatment is required lifelong. Recent clinical studies have trialed latency-reversing agents (LRA) as a method to eliminate latently infected cells; however, the effects of LRA on the central nervous system (CNS), a well-known site of virus persistence on cART, are unknown. In this study, we evaluated the toxicity and potency of a panel of commonly used and well-kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 37 publications
1
38
0
Order By: Relevance
“…These data are in agreement with previous studies showing no increase in HIV‐1 production by LRAs in persistently infected astrocytes (Chauhan, ; Li et al, ). However, other studies reported some reactivation with bryostatin (Diaz et al, ), JQ1 and various HDAC inhibitors (Gray et al, ; Narasipura et al, ). Differences in experimental methodologies may account for the discrepant findings.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These data are in agreement with previous studies showing no increase in HIV‐1 production by LRAs in persistently infected astrocytes (Chauhan, ; Li et al, ). However, other studies reported some reactivation with bryostatin (Diaz et al, ), JQ1 and various HDAC inhibitors (Gray et al, ; Narasipura et al, ). Differences in experimental methodologies may account for the discrepant findings.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, the high concentration of SAHA used in this study (i.e., 10 μM) was toxic when we used it with HFA (data not shown). Gray et al reported that some LRAs promote HIV‐1 transcription in HFA (Gray et al, ). However, they only monitored HIV‐1‐specific RNA levels, which do not necessarily reflect protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…Along with CD4 ϩ T cells, macrophages and microglial cells are targets of HIV infection in vivo and are associated with neurocognitive disorders and tissue pathology, especially during the late stages of AIDS, when T cells are depleted (6)(7)(8)(9)(10)(11). Several distinct features of HIV replication in macrophages underscore their key role as potential viral reservoirs (12,13), including (i) relative resistance to the cytopathic effects of HIV compared to T cells (14); (ii) harboring replication-competent virus for up to several weeks (15); (iii) residing within lymphoid tissues, where antiretroviral drug (ARV) penetration is reduced (16)(17)(18); and (iv) viral accumulation within surface-connected compartments (19)(20)(21) that are inaccessible to neutralizing antibodies (6).…”
mentioning
confidence: 99%
“…This means it is anatomically able to target any latently infected cells residing within the CNS. However, Gray et al found it did not induce viral transcription in monocyte-derived macrophages, a cellular model for brain perivascular macrophages and microglia, or primary foetal astrocytes [50]. This result is disappointing: if reproducible in vivo, disulfiram may not improve the cognitive decline of HIV patients.…”
Section: Discussionmentioning
confidence: 99%